Seleção de ingredientes ativos para o desenvolvimento de iscas tóxicas para o controle de formigas-cortadeiras (Hymenoptera: Formicidae) - Bueno, Fabiana Correa [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Since 2009 when sulfluramid was listed in annex B of the Stockholm Convention's Persistent Organic Pollutants, effort has been made to search for other active ingredients to use in baits for controlling leaf-cutting ants in Brazil. Considering active ingredients that inhibit insect cellular respiration have been shown to be effective in controlling ants, the current work aimed at assessing the effects of diafenthiuron and tolfenpyrad to Atta sexdens rubropilosa workers through toxicological bioassays and morphological analysis of the ventricle, Malpighian tubules and the post-pharyngeal glands to develop toxic baits with new active ingredients. Diafenthiuron and tolfenpyrad were dissolved in acetone and in a solution of acetone + soy oil then incorporated in artificial diet at concentrations of 1 μg/mL, 5 μg/mL, 10 μg/mL, 50 μg/mL, 100 μg/mL, 500 μg/mL and 1000 μg/mL. Workers with body mass between 15 and 25 mg were distributed in 50 ants for each treatment, divided into groups of 10 and maintained in 5 Petri dishes. For each active ingredient, two test batteries were performed, one for analysis of toxicity and other for morphological analysis. The Petri dishes were placed in a BOD incubator at 24 º C ± 1 º C and relative humidity above 70%. The battery of toxicity analysis was examined daily for mortality annotation over a period of 25 days. For morphological analysis, five workers from each treatment were collected on the 4th day, dissected and removed organs were fixed and processed for inclusion in historesin. Histological sections were stained with hematoxylin-eosin and documented in light microscope Motic BA 300. According to toxicity tests, diafenthiuron in concentrations of 5.000 g/g (0.5%), 10.000 g/g (1%) and 50.000 g/g (5%) and tolfenpyrad in concentrations of 500 g/g (0.05%), 1.000 g/g (0.1%) and 5.000 g/g (0.5%) were incorporated into baits and tested in incipient colonies. The treatments where ants...

Desde 2009, quando a sulfluramida foi incluída no anexo B da Convenção de Estolcomo sobre Poluentes Orgânicos Persistentes, há uma procura por ingredientes ativos substitutos para uso em iscas no controle de formigas-cortadeiras no Brasil. Considerando que os ingredientes ativos responsáveis pela inibição da respiração celular dos insetos têm apresentado resultados satisfatórios no controle de formigas, o presente trabalho objetivou avaliar os efeitos do diafentiurom e do tolfenpyrad em operárias de Atta sexdens rubropilosa, por meio de bioensaios toxicológicos e da análise morfológica do ventrículo, dos túbulos de Malpighi e das glândulas pós-faríngeas para o desenvolvimento de iscas tóxicas. Os ingredientes ativos dissolvidos em acetona e em uma solução de acetona + óleo de soja foram incorporados em dieta artificial nas concentrações 1 μg/mL, 5 μg/mL, 10 μg/mL, 50 μg/mL, 100 μg/mL, 500 μg/mL e 1000 μg/mL. Para a realização dos bioensaios, operárias com massa corpórea entre 15 a 25 mg foram distribuídas em lotes de 50 formigas para cada tratamento, divididas em grupos de 10 e mantidas em 5 placas de Petri. Para cada ingrediente ativo, foram montadas duas baterias de testes, uma para análise de toxicidade e outra para análise morfológica. As placas foram colocadas em estufa para B.O.D com temperatura de 24ºC + 1ºC e umidade relativa acima de 70%. A bateria relativa à análise de toxicidade foi examinada diariamente para anotação da mortalidade durante um período de 25 dias. Para a análise morfológica, 5 operárias de cada tratamento foram coletadas no 4º dia de experimento, dissecadas e os órgãos removidos foram fixados e processados para inclusão em historesina. As secções histológicas foram coradas com Hematoxilina–Eosina e fotodocumentadas em fotomicroscópio Motic BA 300. De acordo com os resultados obtidos nos testes de toxicidade, o diafentiurom nas concentrações 5.000...
Keywords: Formiga; Repelentes e iscas insetos; Formiga-cortadeira; Toxicidade - Testes; Toxicologia; Morfologia (Animais); Intoxicação